A combination of four Toxoplasma gondii nuclear-targeted effectors protects against interferon gamma-driven human host cell death - Brittany Henry; Aubrey J. Phillips; L. David Sibley; Alex Rosenberg (mBio, 2024)
ABSTRACT In both mice and humans, Type II interferon gamma (IFNγ) is crucial for the regulation of Toxoplasma gondii (T. gondii) infection, during acute or chronic phases. To thwart this defense, T. gondii secretes protein effectors hindering the host’s immune response. For example, T. gondii relies on the MYR translocon complex to deploy soluble dense granule effectors (GRAs) into the host cell cytosol or nucleus. Recent genome-wide loss-of-function screens in IFNγ-primed primary human fibroblasts identified MYR translocon components as crucial for parasite resistance against IFNγ-driven vacuole clearance. However, these screens did not pinpoint specific MYR-dependent GRA proteins responsible for IFNγ signaling blockade, suggesting potential functional redundancy. Our study reveals that T. gondii depends on the MYR translocon complex to prevent parasite premature egress and host cell death in human cells stimulated with IFNγ post-infection, a unique phenotype observed in various human cell lines but not in murine cells. Intriguingly, inhibiting parasite egress did not prevent host cell death, indicating this mechanism is distinct from those described previously. Genome-wide loss-of-function screens uncovered TgIST, GRA16, GRA24, and GRA28 as effectors necessary for a complete block of IFNγ response. GRA24 and GRA28 directly influenced IFNγ-driven transcription, GRA24’s action depended on its interaction with p38 MAPK, while GRA28 disrupted histone acetyltransferase activity of CBP/p300. Given the intricate nature of the immune response to T. gondii, it appears that the parasite has evolved equally elaborate mechanisms to subvert IFNγ signaling, extending beyond direct interference with the JAK/STAT1 pathway, to encompass other signaling pathways as well.IMPORTANCEToxoplasma gondii, an intracellular parasite, affects nearly one-third of the global human population, posing significant risks for immunocompromised patients and infants infected in utero. In murine models, the core mechanisms of IFNγ-mediated immunity against T. gondii are consistently preserved, showcasing a remarkable conservation of immune defense mechanisms. In humans, the recognized restriction mechanisms vary among cell types, lacking a universally applicable mechanism. This difference underscores a significant variation in the genes employed by T. gondii to shield itself against the IFNγ response in human vs murine cells. Here, we identified a specific combination of four parasite-secreted effectors deployed into the host cell nucleus, disrupting IFNγ signaling. This disruption is crucial in preventing premature egress of the parasite and host cell death. Notably, this phenotype is exclusive to human cells, highlighting the intricate and unique mechanisms T. gondii employs to modulate host responses in the human cellular environment.